Internet of Things Analystics Menggunakan ELK Stacks Dalam Pabrik Perangkat Server - Bryant, Kent; Mulyadi, Melisa; Panjaitan, MM Lanny; Angela Kartawidjaja, Maria; Rippun Gideon Manalu, Ferry (Jurnal Elektro, 2023)
The internet is an information and communication technology that makes it easier for human activities to access data and send information into networks. For industry, the internet is also used to store data both internally and externally. There are several application facilities that are open source to help the industry save data via the internet to the cloud, one of which is the ELK stack. In this research, a simulation of a temperature and humidity monitoring system is designed for a server device factory and simultaneously calculates the amount of production. The data obtained is sent to Elasticsearch as a cloud so that the measurement data can be monitored and visualized in the form of graphs. The system is realized using a microcontroller, ESP8266, DHT11 sensor and proximity sensor. This design is equipped with an ELK system that can collect data and filter the required data so that it can be monitored and visualized in real time. The results of testing the temperature and humidity obtained are in the optimal value range and also proves that this research can be used on a large scale. It is recommended that this design be implemented in a factory or smart home to make it easier to obtain and retrieve the required data.